Adsorption Properties of Malaysian Activated Carbon for Use in Solar Refrigerator - Nyein, Chan Win @ Mohd. Ali (2002)
Detail experiments and analyses have been made on the solar refrigerator using activated charcoal and methanol adsorption cycle. A test rig was designed to study adsorption and desorption capability of activated carbon. A comparison has been made between adsorbability of six Malaysian commercial activated carbons. To improve the adsorbability of the carbon a simple method was tested. Base on Dubinin equation, some them10dynamic properties of adsorbent adsorbate necessary for refrigeration calculation had been obtained. In this experiment methanol is used as the refrigerant medium. The amollnt of methanol adsorbed by the activated carbon was measured as a function of temperature of the activated carbon. During the experiment, the temperature of the unadsorbed methanol was kept constant. From Dubinin-Astakhov equation, parameters of adsorption data were determined using graphical analysis. A Claperyon P-T-X (pressure, temperature and concentration) diagram was then constructed.